2013
DOI: 10.1088/2040-8978/15/6/064005
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative rogue wave generation in multiple-pulsing mode-locked fiber laser

Abstract: Following the first experimental observation of a new mechanism leading to optical rogue wave (RW) formation briefly reported in Lecaplain et al (2012 Phys. Rev. Lett. 108 233901), we provide an extensive study of the experimental conditions under which these RWs can be detected. RWs originate from the nonlinear interactions of bunched chaotic pulses that propagate in a fiber laser cavity, and manifest as rare events of high optical intensity. The crucial influence of the electrical detection bandwidth is ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
2
39
0
5
Order By: Relevance
“…2 (b)) and the shape of optical spectrum (Fig. 2 (c)) reveal soliton rain similar to the observed in literature [1][2][3][4][5]. The main difference is in low pump power of 67 mW used here vs 800 mW used by the other authors [1][2][3][4][5].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…2 (b)) and the shape of optical spectrum (Fig. 2 (c)) reveal soliton rain similar to the observed in literature [1][2][3][4][5]. The main difference is in low pump power of 67 mW used here vs 800 mW used by the other authors [1][2][3][4][5].…”
Section: Resultssupporting
confidence: 84%
“…This makes such lasers perfect test bed systems to study RWs in the context of origin and mitigation with further results application in numerous disciplines -social sciences, natural sciences and technology & engineering [1][2][3][4][5]. In MLFLs, adjacent pulses interact through their tails overlapping or through the dispersive waves.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, mode-locked lasers (MLL) are perfect test bed systems to study RWs origin and techniques of mitigation with potential to apply results beyond the scope of photonics [8][9][10][11][12]. The femtosecond/picosecond pulsewidth range and MHz/GHz repetition rate of pulses in MLL provides an opportunity to observe more data on rogue waves in the form of bunches of noise-like pulses (soliton rain) in the short time frame and under laboratory-controlled conditions [8][9][10][11][12]. It has been found that RWs are emerging in MLL as a result of interaction of pulses (dissipative solitons) through their tails overlapping or through the dispersive waves [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The femtosecond/picosecond pulsewidth range and MHz/GHz repetition rate of pulses in MLL provides an opportunity to observe more data on rogue waves in the form of bunches of noise-like pulses (soliton rain) in the short time frame and under laboratory-controlled conditions [8][9][10][11][12]. It has been found that RWs are emerging in MLL as a result of interaction of pulses (dissipative solitons) through their tails overlapping or through the dispersive waves [8][9][10][11][12]. Such interaction is accompanied by recirculation of pulses in a ring cavity and so results in coupling enhancement and creating chaotic bunching at the time scales shorter than a round-trip time [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in the context of mode-locked fiber lasers, the ORW mostly have been observed at regimes of chaotic bunches of noise-like pulses or soliton rain [3]. Also, it has been found that ORW can be generated in mode-locked lasers as a result of the interaction of dissipative solitons interacting through overlapping of their tails or by dispersive pulses [4]. An extensive study of the mechanisms of formation of ORWs have been done either experimentally or theoretically in fiber lasers with nonlinearly driven cavities [5], Raman fiber amplifiers and lasers [6] and fiber lasers via modulation of pump [7].…”
Section: Introductionmentioning
confidence: 99%